The potential of big data and telecommunications in the Ebola response - Daniel Hellmann; Jennifer Chan; Andrea Tapia; Carleen F. Maitland (International Telecommunications Society (ITS), 2015)
Telecommunications infrastructure plays a critical role in crisis response, whether in natural disasters or health crises such as the West African Ebola response. For these latter cases, where infrastructure damage is not a problem, the crisis generates increased demands on systems already plagued by sparse coverage and limited bandwidth. Recently, the potential benefits of big data analytics has increased the demands on these networks. In turn, this generates pressure on the network operators to upgrade facilities and may present opportunities for third party support. If designed properly, these improvements may create network improvements that persist beyond the crisis. This article examines the dampening effect of network infrastructure on data sharing and its effects for the promise of 'Big Data' as well as the role of third party organizations, namely humanitarian organizations and their private sector and donor partners, in enhancing network capacity. Through a case study of the West African Ebola response, we specify the network infrastructure limitations as well as collaborative efforts at improving infrastructure for the response and the long term. The research sheds light on the role crisis telecommunications can play in enhancing infrastructure, building a bridge between disaster and development efforts and associated scholarship [1]-[4]. The research also provides recommendations as to mechanisms regulators might use to foster collaboration and ease the path for humanitarian organizations seeking to solve long standing network problems, even if only to meet short term needs.
Keywords: 330